MERAJUT KESADARAN LINGKUNGAN MELALUI CERITA ANAK LUH AYU MANIK MAS KARYA NI NYOMAN AYU SUCIARTINI: KAJIAN EKOKRITIK - Wardani, Kadek Devi Kalfika Anggria; Gorda, Anak Agung Ngurah Eddi Supriyadinata (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2024)
Environmental damage has become an urgent global issue, including in Indonesia. Related to these problems, environmental education through children's story media can be used as a strategic approach to instill ecological awareness from an early age. One of the relevant children's literary works used is Luh Ayu Manik Mas: Ngelawan Luu Plastik, which not only raises environmental issues but also integrates local wisdom values. By using an ecocriticism approach, this study aims to analyze how the relationship between humans and nature is represented in children's stories. The research uses a content analysis method with a ecocritism approach, which focuses on three main aspects: environmental criticism, environmental education, and local wisdom. The results of the study show that this story conveys a strong criticism of the use of single-use plastics and their impact on ecosystems, such as coastal pollution and threats to marine life. Environmental education is present through dialogue that encourages readers to play an active role in reducing plastic waste. In addition, the local wisdom of the Hindu community in Bali is also depicted in the narrative of the story through a number of rituals, daily life practices that prioritize sustainability, and the philosophy of Tri Hita Karana to promote harmony between humans, nature, and spirituality. Thus, this story is not only an effective educational medium, but also serves as a means of preserving relevant local cultural values to face global environmental challenges.